Does video training increase adult and child joint attention and improve child outcomes? Two individual case studies in children with autism spectrum disorder. - Benson, Rhianna; Joosten, Annette (Taylor & Francis, 2014)
Background: Children with autism spectrum disorder experience difficulty initiating (IJA) and responding to joint attention (RJA), which is critical to engagement in social interactions. The adult role in developing joint attention is widely accepted, but measurement of outcomes from adult training is rarely reported. Method: Using a single case study design, this pilot study examined the joint attention of 1 adult and 2 children before and after the adult was trained using video feedback, to recognise joint attention opportunities and strategies to increase children's joint attention. Results: There was a statistically significant increase in adult IJA and a corresponding increase in the children's RJA. Adult RJA increased minimally in response to minimal increase in the children's IJA. Visible increases in adult–child engagement occurred, but the activity chosen, documentation requirements, and one training session also influenced outcomes. Conclusions: This study provides preliminary evidence that video training does increase adult joint attention attempts and improves social interaction and engagement in activities. Other factors affecting adult and child joint attention frequency are also identified.